2016
DOI: 10.1016/j.rser.2015.12.071
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the valorization of waste and by-product materials as thermal energy storage (TES) materials

Abstract: Today, one of the biggest challenges our society must face is the satisfactory supply, dispatchability and management of the energy. Thermal Energy Storage (TES) has been identified as a breakthrough concept in industrial heat recovery applications and development of renewable technologies such as concentrated solar power (CSP) plants or compressed air energy storage (CAES). A wide variety of potential heat storage materials has been identified depending on the implemented TES method: sensible, latent or therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 127 publications
(61 citation statements)
references
References 69 publications
(94 reference statements)
0
61
0
Order By: Relevance
“…In addition to thermal properties, the acoustical demand of buildings, including sound absorption and sound insulation, is of great importance in order to reduce the impact of urban noise [8,26]. The thermal and acoustic properties of biomass materials have been widely studied recently [27,28]. Asdrubali et al [16] reported on the various types of unconventional sustainable insulation materials, including natural and recycled ones, in order to emphasize the environmental advantages of using these materials.…”
Section: Biomass Materials In Building Constructionmentioning
confidence: 99%
“…In addition to thermal properties, the acoustical demand of buildings, including sound absorption and sound insulation, is of great importance in order to reduce the impact of urban noise [8,26]. The thermal and acoustic properties of biomass materials have been widely studied recently [27,28]. Asdrubali et al [16] reported on the various types of unconventional sustainable insulation materials, including natural and recycled ones, in order to emphasize the environmental advantages of using these materials.…”
Section: Biomass Materials In Building Constructionmentioning
confidence: 99%
“…Latent heat thermal energy storage (LHTES) using phase change materials (PCMs) have developed into an important way to improve energy efficiency in heat recovery [1,2]. In general, a suitable PCM should have a high latent heat per unit volume and a constant phase transition temperature [3].…”
Section: Introductionmentioning
confidence: 99%
“…Within this scenario, byproducts are highlighted as emergent materials to be considered as TES candidates as reported by Barreneche et al (2013Barreneche et al ( , 2014 [21,22] and Ortega et al [23,24], where slags were studied as TES media. Moreover, Gutierrez et al have stated the feasibility of revalorizing wastes or by-products as TES materials although more studies are needed to achieve its industrial deployment [25].…”
Section: Introductionmentioning
confidence: 99%